Galvanically Replaced, Single‐Bodied Lithium‐Ion Battery Fabric Electrodes. (20th February 2020) - Woo, Sang‐Gil; Yoo, Sijae; Lim, Si‐Hyoun; Yu, Ji‐Sang; Kim, Kyungbae; Lee, Jaegab; Lee, Donggue; Kim, Jae‐Hun; Lee, Sang‐Young
Abstract: Despite extensive research on flexible/wearable power sources, their structural stability and electrochemical reliability upon mechanical deformation and charge/discharge cycling have not yet been completely achieved. A new class of galvanically replaced single‐bodied lithium‐ion battery (LIB) fabric electrodes is demonstrated. As a proof of concept, metallic tin (Sn) is chosen as an electrode active material. Mechanically compliable polyethyleneterephthalate (PET) fabrics are conformally coated with thin metallic nickel (Ni) layers via electroless plating to develop flexible current collectors. Driven by the electrochemical potential difference between Ni and Sn, the thin Ni layers are galvanically replaced with Sn, resulting in the fabrication of a single‐bodied Sn@Ni fabric electrode (Sn is monolithically embedded in the Ni matrix on the PET fabric). Benefiting from the chemical/structural uniqueness and rationally designed bicontinuous ion/electron transport pathways, the single‐bodied Sn@Ni fabric electrode provides exceptional redox reaction kinetics and omnidirectional deformability (notably, origami‐folding boats), which lie far beyond those attainable with conventional LIB electrode technologies. Abstract : A galvanically replaced single‐bodied Sn@Ni fabric electrode is presented as a new approach for developing high‐performance lithium‐ion battery (LIB) electrodes with exceptional redox reaction kinetics and omnidirectional deformability. Benefiting from the chemical/structural uniqueness, the single‐bodied Sn@Ni fabric electrode provides significant improvements in electrochemical performance and mechanical flexibility, which lie far beyond those attainable with conventional LIB electrode technologies.